2018
DOI: 10.18677/agrarian_academy_2018b16
|View full text |Cite
|
Sign up to set email alerts
|

Rentabilidade Econômico-Financeira Para Implantação Da Banana Prata Anã

Abstract: RESUMO A banana está entre as frutíferas de maior presença na mesa do consumidor no diaa-dia. A excelente aceitação da fruta está relacionada aos aspectos sensoriais e ao valor nutricional, boa fonte energética, devido à presença de carboidratos, minerais como o potássio, e vitaminas. Objetivou-se neste trabalho analisar a rentabilidade financeira do cultivo da banana prata anã na fazenda experimental da Universidade Estadual de Goiás (UEG) localizada no Sudeste de Goiás. Foram realizadas análises de custos a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 8 publications
1
3
0
3
Order By: Relevance
“…Culture treatments increased in % due to the expectation of production from the 1st year to the 2nd year; on the other hand, irrigation costs decreased, since the highest cost occurred in the system implementation in the 1st year of cultivation (Table 3). The same behavior was described by Pacheco et al (2016), Rodrigues et al (2018) and Do Couto et al (2020). Costs with seedlings, area preparation, inputs and labor for implantation and management of the banana plantation, excluding costs related to irrigation and application of the alternative treatment, accounted for most of the effective operational cost, about 85.1% in the first year and 88.5% in the second year.…”
Section: Resultssupporting
confidence: 80%
See 3 more Smart Citations
“…Culture treatments increased in % due to the expectation of production from the 1st year to the 2nd year; on the other hand, irrigation costs decreased, since the highest cost occurred in the system implementation in the 1st year of cultivation (Table 3). The same behavior was described by Pacheco et al (2016), Rodrigues et al (2018) and Do Couto et al (2020). Costs with seedlings, area preparation, inputs and labor for implantation and management of the banana plantation, excluding costs related to irrigation and application of the alternative treatment, accounted for most of the effective operational cost, about 85.1% in the first year and 88.5% in the second year.…”
Section: Resultssupporting
confidence: 80%
“…In a study carried out by Pacheco et al (2016) during the implementation of a banana plantation in Aquidauana, Mato Grosso do Sul, costs on inputs represented 46.23% of the EOC due to the need to purchase seedlings, plastic bags and greater use of fertilizers. Rodrigues et al (2018) evaluated the economic and financial profitability for the implementation of a 'Prata Anã' banana plantation in Ipameri, Goiás, and found that inputs represented the highest costs in the year of crop implementation, representing 74.06% of the total operation cost (TOC) for the activity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Para a implantação do bananal foi considerado o preparo do solo com calagem, aração e gradagem, além disso, designou-se a aplicação de cloreto de potássio na dosagem de 200 kg.ha -1 , antes da data prevista para o plantio e o NPK com a formulação 10 -10 -10, em aproximadamente 350 gramas em cada cova. Optou-se pelo plantio manual em covas a uma profundidade de 35 cm e o espaçamento de 3,0 X 3,0 m entre mudas de banana da variedade Prata-Anã, estabelecendo um estande de 1.111 plantas.ha -1 , no entanto, foram contabilizadas 1.300 mudas, conforme proposto pelos autores Rodrigues et al (2018a). A colheita foi estabelecida em média 365 dias após o plantio, comercializando os frutos in natura.…”
Section: Methodsunclassified